Diversity in the classroom: Addressing diverse learning and creating inclusive spaces for interdisciplinary interaction - Garcia, Nerea Turreira (Improving University Science Teaching and Learning, 2023)
This study tests participatory research methods to address diversity in learning and to create awareness of the students’ personal needs and their classmates’ needs. Thus, the methods applied aim to promote a safe, inclusive and comfortable space for teaching and learning in international higher education programs. Ultimately, the study aims to help establish the internationalization strategy of the University of Copenhagen in practice.